Face Masks Considerably Reduce Covid-19 Cases in Germany - A Synthetic Control Method Approach - Timo Mitze; Reinhold Kosfeld; Johannes Rode; Klaus Wälde (Center for Economic Studies and Ifo Institute (CESifo), 2020)
We use the synthetic control method to analyze the effect of face masks on the spread of Covid-19 in Germany. Our identification approach exploits regional variation in the point in time when wearing of face masks became mandatory in public transport and sales shops. Depending on the region we consider, we find that face masks reduced the number of newly registered SARS-CoV-2 infections between 15% and 75% over a period of 20 days after their mandatory introduction. Assessing the credibility of the various estimates, we conclude that face masks reduce the daily growth rate of reported infections by around 47%.
Keywords: 330; Covid-19; public health measures; face masks; synthetic control method